La participation des groupes communautaires au musée : quelles logiques et pour quels effets ? Le cas de l’exposition InterReconnaissance à l’Écomusée du fier monde - Maignien, Noémie; Lamoureux, Ève; Saillant, Francine (Muséologies)

(untitled) (Association Québécoise de Promotion des Recherches Étudiantes en Muséologie (AQPREM), 2023)
Begun in 2018, the action-research project Accessibilité des publics marginalisés au musée: des outils adaptés (Museum accessibility for marginalized publics: adapted tools) wished to include the publics in a reflection on inclusion in the museum. The initiative was undertaken after a research project InterReconnaissance, La mémoire des droits dans le milieu communautaire au Québec (2012-2017), as well as the InterReconnaissance, une mémoire citoyenne se raconte exhibition (Écomusée du fier monde, 2018-2019). This vast endeavour explored “the stories behind the story,” that is, the battles to defend and promote minority group rights since the 1960s.The research-action project was based on the observation that the museal milieu faced a lack of knowledge, experience and resources to conceive accessibility for certain groups, most notably people living with mental health issues, handicaps and issues related to recent immigration. It was also necessary to make the exhibition accessible to communities within it and involved in its realization. This wish guided the team, composed of researchers, an artist and a cultural mediator, to consult with three groups concerned with mobilizing community networks and defending rights historically constituted and organized around, by and for these populations. This step then led to the creation and realization of cultural mediation activities adapted and developed in conjunction with the community movement.Two stances characterized the project. While they are not mutually exclusive, they delineate the trends that can shed a novel light on the actions and role of museums. The first is defined by an anthropological research approach that allows the recounting of history through the memory of its principal actors. It is also revealed by the polyphonic approach of the exhibition and the validation of these people, their actions and their impact on Quebec society. The exhibition thus makes another history visible and promotes acknowledgement of it by bringing it into the museum, contributing to the defense of rights.The other rationale is rooted in a consideration of the conditions encouraging museum visits by the most marginalized groups through concerted action with community organizations. It is the foundation of a variety of strategies adopted to create an activity of cultural mediation and co-creation to meet the needs and wishes of the invitees, as well as contributing to an activity that is meaningful for the groups, by pursuing the goals of appropriating and transmitting knowledge, but also self-emancipation and self-expression. Here, the project is based more on a logic of inclusion that museums have increasingly adopted in recent years.In this article, we propose a theoretical exploration of these two approaches. It also allows us to analyze the participation of the publics in light of the principles of the museal tradition of ecomuseology. In addition to painting a reflective and critical portrait of our action and the project we have dedicated ourselves to in recent years, we think that this work will encourage reflection on the effect of different participatory modes of the publics at the museum, particularly groups experiencing exclusion. We also hope that it will help illuminate museal action and the various possible dimensions of the museum’s social role.